Design of Squarer Circuit in Sub-threshold Mode - Thakral, Bindu; Vaish, Arti; Koteswara Rao Alla, Rama (International Journal of Engineering and Technology, 2018)
Historically, analog designs have been assumed as a voltage mode based signal processing. However, the necessity of high speed circuits operating at reduced supply voltage has lead to a development of new circuit topology referred as current-mode designs. For low power low voltage designs the applications using translinear principle based circuits has become an area of research and interest. It has wide application in nonlinear signal processing and to build basic active elements. Mode of MOS transistor used in analog circuit realization of is important parameter deciding the performance of the circuit. In this paper, a squarer circuit is proposed based on sub threshold-mode MOS transistors exhibiting the exponential current-voltage characteristic. The simulations have been performed on model files of TSMC 0.18 micrometer technology with the help of ELDO Simulator.Â